Mental health services for minority ethnic children and adolescents - Malek, Mhemooda; Joughin, Carol (London ; New York : Jessica Kingsley Publishers, 2004)
Bringing together current research on mental health services for children from minority ethnic backgrounds, this much-needed resource provides guidance for both practice and policy. In the light of their interviews with child and adolescent mental health managers about their approaches to service development, the authors argue that the delivery of effective services can be achieved only by recognizing the diversity of cultures and individual needs of minority groups and encouraging more communication between service providers. They consider how ethnicity is defined, and how the field of mental.
Cover; Mental Health Services for Minority Ethnic Children and Adolescents; Contents; Foreword -- Kedar Nath Dwivedi; Acknowledgements; Preface; Introduction -- Mhemooda Malek; Recommendations -- FOCUS; Part One; 1 Understanding Ethnicity and Children's Mental Health; 2 The Cultural Relevance of the Mental Health Disciplines; 3 The Epidemiology of Mental Health Problems in Children and Adolescents from Minority Ethnic Groups in the UK; 4 Meeting the Needs of Minority Ethnic Groups in the UK; 5 Refugee Children in the UK; Part Two; Survey Methods and Findings.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Children of minorities -- Mental health services -- Great Britain; Minority teenagers -- Mental health services -- Great Britain; Children of minorities -- Mental health -- Great Britain; Minority teenagers -- Mental health -- Great Britain; Child mental health services -- Social aspects -- Great Britain; Child psychiatry -- Social aspects; Adolescent psychiatry -- Social aspects; Mental health services; Children; Cultural pluralism; Needs assessment; Mental Health Services; Child; Cultural Diversity; Ethnicity -- psychology; Health Care Surveys -- methods; Mental Disorders -- ethnology; Minority Groups -- psychology; Needs Assessment; United Kingdom; Enfants issus des minorités -- Services de santé mentale -- Grande-Bretagne.; Adolescents issus des minorités -- Services de santé mentale -- Grande-Bretagne.; Enfants issus des minorités -- Santé mentale -- Grande-Bretagne.; Adolescents issus des minorités -- Santé mentale -- Grande-Bretagne.; Enfants -- Services de santé mentale -- Aspect social -- Grande-Bretagne.; Enfants -- Psychiatrie -- Aspect social; Adolescents -- Psychiatrie -- Aspect social; Services de santé mentale; Enfants; Diversité culturelle; Analyse des besoins; children (people by age group); needs assessment; Pathology; Counselling & Advice Services; PSYCHOLOGY -- Mental Health; PSYCHOLOGY -- Mental Illness; MEDICAL -- Mental Health; Needs assessment; Mental health services; Cultural pluralism; Children; Children of minorities -- Mental health; Children of minorities -- Mental health services; Great Britain; Geestelijke gezondheidszorg; Etnische minderheden